Low‐carbohydrate diets for overweight and obesity: a systematic review of the systematic reviews. (7th September 2018) - Churuangsuk, C.; Kherouf, M.; Combet, E.; Lean, M.
Summary: Low‐carbohydrate diets are being widely recommended, but with apparently conflicting evidence. We have conducted a formal systematic review of the published systematic reviews of RCTs between low‐carbohydrate vs. control (low‐fat/energy‐restricted) diets in adults with overweight and obesity. In MEDLINE, Embase, Web of Knowledge and Cochrane Database of Systematic Reviews, searched from inception to September 2017, we identified 12 systematic reviews, 10 with meta‐analyses. Differences in methods, study quality, weight change and citations of published systematic reviews were assessed by AMSTAR‐2. Review methods varied in definitions of low‐carbohydrate diet, databases searched and bias assessment. Overall review quality was high in two, moderate in three, critically low in seven. Among meta‐analyses, 4/5 with critically low quality showed low‐carbohydrate diet superiority for weight loss (0.7–4.0 kg), while high quality meta‐analyses reported little or no difference between diets. Greater numbers of participants correlated with smaller differences in weight loss ( r = 0.73, p = 0.03). More citations correlated with lower review quality (rho = −0.9, p = 0.037), with larger differences in weight loss (rho = −0.9, p = 0.037), and with journal impact factor (rho = 1.0, p = 0.01). In conclusion, publication acceptance and citations appear to favour apparently larger effect sizes above methodological quality. Better quality reviews and RCTs are needed, before recommending low‐carbohydrate diets as preferred to other approaches for energy restriction.